The World book encyclopedia : vol. 1 - World Book, Inc. (Chicago : World Book, 1990)
An encyclopedia designed especially to meet the needs of elementary, junior high, and senior high school students.
Includes bibliographical references and index.
Keywords: Encyclopedias and dictionaries; Encyclopedias and dictionaries